Polarity Inversion Strategy for Nickel-Catalyzed Reductive Coupling of Aldehydes with Alkenyl Halides - Odagaki, Shuto; Sudo, Ko; Kawabe, Kosuke; Kurahashi, Takuya (Synlett, 2025)
We report a nickel-catalyzed reductive cross-coupling strategy for the stereoconvergent synthesis of allyl alcohols from aldehydes and alkenyl halides. Despite the synthetic importance of allyl alcohols, achieving their stereoselective construction remains a considerable challenge. To date, no nickel-catalyzed reductive cross-coupling between aldehydes and alkenyl halides has been reported. In this study, activation of aldehydes with silyl groups enables their selective oxidative addition to low-valent nickel. Following oxidative addition and subsequent single-electron reduction, polarity inversion is proposed to generate a nucleophilic alkyl–nickel intermediate, which selectively undergoes cross-coupling with electro-philic alkenyl halides to afford allyl alcohols.
Keywords: Alcohols; Aldehydes; Catalysis; Coupling; Transition metals